METHODS OF LEARNING INDONESIAN LANGUAGE: ETHNOPRAGMA-EDUCATIVE PERSPECTIVE IN HIGH SCHOOL (METODE PEMBELAJARAN BAHASA INDONESIA DI SMA BERBASIS ETNOPRAGMA-EDUCATIF) - Dewa Ayu Widiasri; Nidya Fitri; Raihan S. Farhan (Jurnal Gramatika, 2022)
The problems discussed in this study are based on the transition of curriculum changes that often change by government policies and the dominance of the use of English. This problem causes Indonesian proficiency value to be categorized as low. For this reason, a learning strategy in Indonesian is needed to minimize all impacts that occur by offering and modifying existing methods called ethnopragma-educative. This study aims to describe learning methods Indonesian in ethnopragma-educative-based high schools (communication ethnography, pragmatics, and educational interactions. The use of methods is carried out with qualitative description in order to be able to accommodate the reality of language in interactions in the classroom. Observation methods carry out the collection of methods, in-depth interviews, documentation with recording techniques, and pragmatics match techniques, and focusing discussion groups with teachers, stakeholders, and communities in the high school environment. The research results were obtained based on the modification of the three statements are (1) the use of communication ethnographic approaches include eight elements, namely setting and scene, participants, ends, an act of sequences, key, instrumentalities, a norm of interaction, and genres able to accommodate learning situations in the classroom to create effective and efficient learning; (2) the use of pragmatic approaches based on illocution, locution, and perlocution actions can maximize the role of teachers as motivators and inspirators in involving students to participate in Indonesian learning to develop cognitive, psychomotor, and achievement of learning go; (3) the use of educational interaction approaches can create two-way learning that is realized by the question and answer method between teachers and students in the classroom